Rethinking balance and impartiality in journalism? How the BBC attempted and failed to change the paradigm. (August 2017) - Wahl-Jorgensen, Karin; Berry, Mike; Garcia-Blanco, Iñaki; Bennett, Lucy; Cable, Jonathan
This article reconsiders the concepts of balance and impartiality in journalism, in the context of a quantitative content analysis of sourcing patterns in BBC news programming on radio, television and online in 2007 and 2012. Impartiality is the cornerstone of principles of public service broadcasting at the BBC and other broadcasters modelled on it. However, the article suggests that in the case of the BBC, it is principally put into practice through juxtaposing the positions of the two main political parties – Conservative and Labour. On this basis, the article develops the idea of the 'paradigm of impartiality-as-balance.' This paradigm prevails despite the news organisation's commitment to representing a broader range of opinion. The paradigm of impartiality-as-balance means that only a narrow range of views and voices are heard on the most contentious and important issues. Further, it results in reporting that focuses on party-political conflict, to the detriment of a journalism which provides much-needed context.